Use Low Cost Phosphorus Sources for Better Nutrition in Aerobic Rice - Yadav, Devideen; Singh, Y. V.; Deepak, Deepak (Indian Farming, 2015)
At present scenario, increase in the price of phosphatic fertilizers is coupled with low recovery (10-30%) of phosphorus. The developing tropical countries like India are attempting to utilize their indigenous reactive ground phosphate rock as a cheaper P source. The problem of water insolubility associated with RPcan be solved through microbial means. Among microbial group PSB and AMF can increase its effectiveness by solubilizing and mobilizing the applied P. Thus inoculation of PSB and AMF with rock phosphate in aerobic rice can increase crop productivity, phosphorus availability and its use efficiency.